Autophagy inhibition restores CD200 expression under IL-1β microenvironment in placental mesenchymal stem cells of fetal origin and improves its pulmonary fibrosis therapeutic potential. (November 2022) - Zhou, Wei; Li, Li; Tao, Jin; Ma, Cunxiang; Xie, Yawei; Ding, Lu; Hou, Shaozhang; Zhang, Zaiqi; Xue, Di; Luo, Jia; Zhu, Yongzhao
Abstract: Background: Mesenchymal stem cells (MSCs) are promising remedies for various inflammatory disease including pulmonary fibrosis (PF). However, the properties of MSCs in PF pathological microenvironment remain unclear. In this study, the efficacy of autophagy in placental mesenchymal stem cells of fetal origin (fPMSCs) in either IL-1β treatment or BLM induced pulmonary fibrosis mice model was examined. Methods: The characteristic of fPMSCs was identified by morphological observation, flow cytometry and differentiation potential. In vitro experiments, fPMSCs were stimulated with IL-1β, to mimic inflammatory microenvironment of pulmonary fibrosis. The immunosuppressive properties and autophagic function in fPMSCs treated with IL-1β were evaluated by both macrophage cells THP-1 activation and the expression of CD200 situation, autophagy marker and MAPK signaling pathway. The in vivo anti-fibrotic activity of fPMSCs interfering autophagy was evaluated by using BLM induced pulmonary fibrosis mice model. Results: fPMSCs belonged to CD73 + CD90 + CD105 + /CD14 - CD34 - CD45 - HLA-DR - cells, and capable differentiation to adipogenic, osteogenic and chondrogenic cells. In addition, immunoinhibitory activity of fPMSCs for macrophage was restrained by IL-1β treatment in CD200 dependent manner. Suppression of autophagy by sh-Atg5 lentivirus increased the expression of CD200 and ratio of CD200 positive fPMSCs, and enhanced fPMSCs immunosuppression for THP-1 activation. Mechanistically, IL-1β induced autophagy regulated by p38 signaling cascade. In vivo, autophagy inhibition induced by Atg5 knockdown in fPMSCs resulted in strengthening antifibrotic effects on PF mice model. Conclusions: Collectively, autophagy derived from inflammatory microenvironment hampered the immunoinhibitory properties of MSCs. Based on this, adjustment of autophagy may be a valid approach to facilitate their immunomodulatory and anti-fibrotic efficacy. Highlights: IL-1βinhibits the expression of CD200 in fPMSCs. IL-1βrestricts immunosuppressive function of fPMSCs for macrophage activation. Autophgy induced by IL-1βdetermined CD200 expression level. IL-1βinduces autophagy via activation of p38 signaling. Inhibiting autophagy enhance therapeutic efficacy of fPMSCs for PF.